Follow-up and treatment of primary HIV infection in Pregnancy - Esra Saglam Kandemir; Sibel Altunisik Toplu; Yasemin Ersoy (Medicine Science, 2022)
The pregnant population infected with "human immunodeficiency virus" (HIV), an important member of the retrovirus family, are encountered with increasing frequency in our clinical experience today. Early and effective suppression of HIV viremia will reduce the risk of mother-to-child transmission of HIV. In the light of the case we aimed to review the antiretroviral treatment (ART) options that can be used in HIV-positive pregnant women and to share an our clinical experience. [Med-Science 2022; 11(2.000): 880-2]